IDENTIFICATION AQUIFER PARAMETERS THROUGH SINGLE WELL PUMPING TEST SERIES AT PT. KALTIM KARIANGAU TERMINAL, BALIKPAPAN, EAST KALIMANTAN - Totok Sulistyo (P3M- Politeknik Negeri Kupang, 2018)
Aquifer Parameters are very important in groundwater and well management. The objective of this research is to determine aquifer parameter in order to be used in determining suitable production rate of well. Research was carried out in PT. Kaltim Kariangau Terminal, which is administratively, located in Balikpapan City, East Kalimantan, Indonesia. PT. Kaltim Kariangau Terminal has developed four wells with distance of each of well is between 50 and 300 meters, but it is a pity because just one well was completed by pumping test without observation well. Result of constant pumping test analyzing through Cooper – Jacob method has shown that value of Transmissivity (T) of aquifer is 319.0718283 m2/day, and it is known from geophysical logging and well construction design that the thickness of aquifer is 48 m, so hydraulic conductivity (K) of aquifer is 6.6473 m/day. Coefficient of aquifer loss is 0.0013 and coefficient of well loss is 0.0000008. Factors development of well could be classified as very effective with the well condition is properly designed and developed.